Effect of crystalline forms (α′ and α) of poly(lactic acid) on its mechanical, thermo-mechanical, heat deflection temperature and creep properties. (September 2016) - Tábi, T.; Hajba, S.; Kovács, J.G.
Graphical Abstract: Highlights: Besides crystallinity, crystalline form (α′ and α) influence the properties of PLA. Deflection temperature of PLA can be highly increased by controlling crystalline form. Creep of PLA can be highly reduced by controlling crystalline form. Abstract: In this paper the effect of crystallinity and crystalline forms (ratio of the less ordered α′ and the more ordered α crystalline forms) of injection moulded Poly(Lactic Acid) (PLA) was analysed on the mechanical, thermo-mechanical, Heat Deflection Temperature (HDT) and creep properties. The injection moulded PLA specimens were post-production annealed in a heat chamber at 80 °C crystallization temperature (Tc ) for 0–60 min to develop various crystallinity as well as at 80–140 °C Tc for one hour to develop various ratios of α′ and α crystal forms with the possible maximum crystallinity. It was demonstrated that not only crystallinity, but also the ratio of the crystalline forms of α′ and α significantly influences the application-wise properties like storage modulus and thus HDT as well as tensile, flexural, impact properties and finally creep characteristics. In most cases better properties (higher HDT, storage modulus, mechanical properties, and creep resistance) could be reached by increasing the α to α′ crystalline form ratio in the PLA specimens.